1999
DOI: 10.1515/bc.1999.050
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Cells Allow High-Level Expression and Formation of Polyomavirus-Like Particles

Abstract: Polyomavirus-derived virus-like particles (VLPs) have been described as potential carriers for encapsidation of nucleic acids in gene therapy. Although VLPs can be generated in E. coli or insect cells, the yeast expression system should be advantageous as it is well established for the biotechnological generation of products for human use, especially because they are free of toxins hazardous for humans. We selected the yeast Saccharomyces cerevisiae for expression of the major capsid protein VP1 of a non-human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 31 publications
6
76
0
Order By: Relevance
“…Yeast-derived recombinant VLPs offer many advantages over other expression systems in terms of protein yield, cost and ease of protein expression (Hale et al, 2002;Sasnauskas et al, 1999). In this study, we found such VLPs to be highly serologically reactive, with an optimum amount of VLPs as low as 6 ng per well.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Yeast-derived recombinant VLPs offer many advantages over other expression systems in terms of protein yield, cost and ease of protein expression (Hale et al, 2002;Sasnauskas et al, 1999). In this study, we found such VLPs to be highly serologically reactive, with an optimum amount of VLPs as low as 6 ng per well.…”
Section: Discussionsupporting
confidence: 52%
“…The polyoma VLPs used in this study were based on the major capsid protein, VP1, and produced in yeast cells from S. cerevisiae (Gedvilaite et al, 2000;Sasnauskas et al, 1999). VLPs of JCV have also been expressed in Escherichia coli and polyomavirus VP1 will also assemble into capsid-like particles in the nucleus of insect cells when expressed in the baculovirus system Ou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The VLPs are empty capsids that consist of the major capsid protein, VP1. The VP1 gene was inserted into the yeast expression vector, pFX7.…”
Section: Polyoma Virus Like Particlesmentioning
confidence: 99%
“…14,15 The mouse monoclonal antibody against JCV and BKV was added in dilution 1/10,000 and incubated for 90 min. 17 Goat anti-Mouse IgG peroxidase conjugate (Southern Biotechnology), diluted 1/1200 in RS-PBS, were rotated for 1 hr before addition to the wells and then reacted for 60 min at room temperature.…”
Section: Igm Confirmation Testmentioning
confidence: 99%
“…The PCR amplification product was digested with BcuI and inserted into XbaIlinearized and dephosphorylated yeast expression plasmid pFX7 under control of yeast GAL1-10 promoter [30] and confirmed by PCR and subsequent DNA sequence analysis. The nucleotide sequence of the amplified PPV VP2 was compared with those in GenBank using the Basic Local Alignment Search Tool (BLAST).…”
Section: Serum Samplesmentioning
confidence: 99%